2015
DOI: 10.1007/s10803-015-2467-9
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem White Matter Predicts Individual Differences in Manual Motor Difficulties and Symptom Severity in Autism

Abstract: Mounting evidence suggests that poorer motor skills may be related to more severe autism symptoms. This study investigated if atypical white matter microstructure in the brain mediated the relationship between motor skills and ASD symptom severity. Sixty-seven males with ASD and 42 males with typical development (5-33 years old) completed a diffusion tensor imaging scan and measures of grip strength, finger tapping, and autism symptom severity. Within the ASD group, weaker grip strength predicted more severe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 58 publications
4
58
0
Order By: Relevance
“…2, Part D), in their autistic participants, between the degree of abnormality in the arcuate and uncinate fasciculi and childhood language symptoms as measured by the Autism Diagnostic Interview-Revised (Le Couteur et al, 2003). At the behavioural level, relationships between movement deficits and autistic symptom severity are well documented in our review (MacDonald, Lord, & Ulrich, 2014;Papadopoulos et al, 2012;Stevenson, Lindley, & Murlo, 2017;Travers et al, 2015Travers et al, , 2013Uljarevic, Hedley, Alvares, Varcin, & Whitehouse, 2017;Colombo-Dougovito & Reeve, 2017 are an exception, but a questionable one due to their methods).…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…2, Part D), in their autistic participants, between the degree of abnormality in the arcuate and uncinate fasciculi and childhood language symptoms as measured by the Autism Diagnostic Interview-Revised (Le Couteur et al, 2003). At the behavioural level, relationships between movement deficits and autistic symptom severity are well documented in our review (MacDonald, Lord, & Ulrich, 2014;Papadopoulos et al, 2012;Stevenson, Lindley, & Murlo, 2017;Travers et al, 2015Travers et al, , 2013Uljarevic, Hedley, Alvares, Varcin, & Whitehouse, 2017;Colombo-Dougovito & Reeve, 2017 are an exception, but a questionable one due to their methods).…”
mentioning
confidence: 75%
“…In a small sample, Hanaie et al (2013) documented abnormalities in the cerebellum, in autistic children, which predicted poorer motor skills and poorer ball skills (these authors did not measure gait). Travers et al (2015) found cerebellar abnormalities to predict tapping speed in autistic children and adolescents. As previously noted, functional communication between the cerebellum and the rest of the motor system was reported to be compromised .…”
Section: The Neuroanatomical Correlates Of Movement Impairmentmentioning
confidence: 95%
See 3 more Smart Citations